'Follow the innovation': A joint experimentation and learning approach to transdisciplinary innovation research - Anna-Katharina Hornidge; Mehmood Ul-Hassan; Peter P. Mollinga (University of Bonn, Center for Development Research (ZEF), 2009)
The ZEF-UNESCO project on Sustainable Management of Land and Water Resources in Uzbekistan addresses the environmental, social and economic problems in the Khorezm province, located within the so-called Aral Sea Zone in Uzbekistan. Currently in its seventh year (third phase), the project aims 'to provide sustainable solutions to the Aral Sea region through a holistic approach, combining technology, policy and institutional options developed in cooperation with local and international stakeholders' as stated on the project website. Consequently, the mutually enriching interplay of multiple disciplines is a precondition for a successful project. Inter- and eventually transdisciplinary research, rather than the mere co-existence of different disciplines captured under the notion of 'multidisciplinarity' is the chosen and actively facilitated approach. A work package is specifically designed to foster the creation of inter- and transdisciplinary research teams around innovation packages developed by the project and identified as possessing 'plausible promises' to take hold in the Khorezm agricultural system. To trigger and sustain this process, a stepwise approach is taken. In a workshop series, four 'Follow the Innovation (FTI)' teams of scientists surrounding innovations were formed, roadmaps prepared and a set of tools and skills for stakeholder interaction taught. A participatory joint experimentation and learning approach was chosen to validate innovations in the farmer's setting. Between the workshops, all four FTI teams are supported and accompanied by a full-time FTI facilitator in their stakeholder outreach and designing and implementing processes of joint experimentation and learning with stakeholders. After the first steps of stakeholder involvement are made and contacts well established, the stakeholders, as partners take part in all following training workshops. Here the further processes of testing, experimenting and jointly adapting the developed innovation packages to match the local needs as well as bio-physical and socio-economic environments are jointly designed with the partners. Additionally this process is continuously monitored, documented, critically discussed and adjusted accordingly by all partners. This paper seeks to illustrate and discuss the experiences collected so far in nurturing a transdisciplinary process of joint experimentation and learning between researchers and local stakeholders, each in their behaviours, attitudes and actions shaped by the context and culture of their places of origin. These include amongst others the academic disciplines of the researchers, the research project, the local Uzbek setting, shaped by strong hierarchical structures and a post-soviet system of knowledge governance. Thus, diverse forms and contents of knowledge, carried by uniquely socialised actors, shall be mutually exchanged and lead to the joint development of new knowledge, to innovations that 'make sense' in the rural setting of Khorezm/Uzbekistan. The process design, its strengths and weaknesses are outlined and recommendations for improvement discussed.
urn:nbn:de:101:1-2009050571
Keywords: 330; Follow-the-Innovation; Follow-the-Technology; transdisciplinary innovation research; innovation diffusion; stakeholder involvement; bottom-up; participatory; joint experimentation and learning approach